A Study of the Secondary School History Curriculum in Chile from Colonial Times to the Present - Zúñiga, Carmen Gloria. author. aut Link
VI, 164 p.
Keywords: "The focus of this book is on the secondary school history curriculum in Chile from colonial times to the present. By way of background, attention is paid to the development of the history curriculum in the three countries which have most influenced educational developments in Chile, namely, England, the United States of America and Spain. The academic literature on the history curriculum throughout the English-speaking and Latin-speaking world, especially on the purposes attached to history as a school subject and the variety of pedagogical approaches prescribed is also considered. The results of a project that addressed the following interrelated research questions are then outlined: • What is the historical background to the current secondary school history curriculum in Chile? • What are the current developments of the secondary school history curriculum in Chile? • What are the issues of concern for secondary school history teachers in Chile? At various times the teaching of the subject ranged from being in the ‘great tradition’ approach, emphasizing teacher-centred activities and repetition of content knowledge, to being in the ‘new history’ tradition, emphasizing the promotion of active learning, student-centred activities and the encouragement of the historical method of enquiry. The analysis also details current issues of concern for teachers regarding the implementation of the current curriculum framework for secondary school history. The book concludes with a consideration of implications for practice in areas pertaining to curriculum development, teaching and learning, management and administration, teacher preparation, and professional development practices in Chile. ".